Modern approaches to formation of civil aviation as an economic branch - Лукьянов, С. Т.; Хороманская, О. Г. (Proceedings of National Aviation University (archive), 1999)
Considered are modern approaches to formation of aviation as an economic branch. Described are elements of legislative part of the process of national regulation of civil aviation activity